Stealing labour: an economic analysis of forced labour and human trafficking - Sarrica, Fabrizio (Researching hidden populations, 2015)
The author approaches trafficking in persons and forced labour from the perspective of the labour market. The basic consideration is that traffickers and exploiters are robbing the communities of victims of trafficking in persons of their most valuable resource: labour. He compares the economic conditions of the labourer and the employer in an exploitative situation against conditions where the labourer is free to choose his or her working conditions. He calculates the economic losses and the benefits in each account of trafficking in persons, revealing who gains and who loses as a result of such crimes. According to the author, not only do forced labour and human trafficking have an economic impact on the victims and their communities, but also society as a whole suffers economic losses when coerced labour is used.